Proposal of a real-time position measurement system for curling stones - Takegawa, Y. (Workshop on Curling Informatics 2018, 2018)
The goal of our study is the design and implementation of a real-time position measurement system for use on curling stones. Often called `chess on ice', curling requires a high level of strategy. Accordingly, how the stones move around the vast curling rink constitutes important data. However, in the unique environment of the icy and vast rink, it is difficult to monitor the position of the stones . In our research, we solve this problem by mounting an infrared LED control module onto each stone and the curling rink carrying out image processing using infrared cameras placed around the rink.